Paving the way to modern growth. Evidence from Bourbon roads in Spain - Miquel-Àngel Garcia-López; Alfonso Herranz-Loncán; Filippo Tassinari; Elisabet Viladecans-Marsal (European Historical Economics Society (EHES), 2021)
This paper analyses the impact that Spanish road construction had on local population growth between 1787 and 1857. We find that the increase in market access associated to road accessibility had a substantial effect on local population growth. The impact was substantially higher on the municipalities that were connected earlier and that had a more diversified occupational structure. By contrast, the effect of the new network on population growth was negative in municipalities close but without direct access to the roads. We interpret these findings as evidence of a process of rural-to-rural migration due to the new roads.
Keywords: H54; N73; N93; 330; roads; accessibility; market access; population growth; pre-railway transport; Spain